2013
DOI: 10.1002/chem.201302526
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient and Selective Palladium‐Catalyzed Aerobic Oxidation of Alcohols

Abstract: An efficient procedure for the oxidation of primary and secondary alcohols to aldehydes and ketones, respectively, with molecular oxygen under ambient conditions has been achieved. By applying catalytic amounts of Pd(OAc)2 in the presence of tertiary phosphine oxides (O=PR3) as ligands, a variety of substrates are selectively oxidized without formation of ester byproducts. Spectroscopic investigations and DFT calculations suggest stabilization of the active palladium(II) catalyst by phosphine oxide ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 91 publications
0
20
0
Order By: Relevance
“…The oxidation of benzylic as well as aliphatic alcohols can be Fig. 1 Proposed mechanism for Pd II /TPO-catalyzed oxidation of alcohols [16] C. Xu et al performed with excellent yield and selectivity towards the corresponding ketones. Low-valent ruthenium complexes such as RuCl 2 (PPh 3 ) 3 are known to catalyze the aerobic oxidation of benzyl alcohol to benzaldehyde, albeit with low rate [18][19][20].…”
Section: ð2þmentioning
confidence: 98%
See 1 more Smart Citation
“…The oxidation of benzylic as well as aliphatic alcohols can be Fig. 1 Proposed mechanism for Pd II /TPO-catalyzed oxidation of alcohols [16] C. Xu et al performed with excellent yield and selectivity towards the corresponding ketones. Low-valent ruthenium complexes such as RuCl 2 (PPh 3 ) 3 are known to catalyze the aerobic oxidation of benzyl alcohol to benzaldehyde, albeit with low rate [18][19][20].…”
Section: ð2þmentioning
confidence: 98%
“…For example, palladium-catalyzed oxidations with tertiary phosphine oxide (TPO), which have been extensively used in cross coupling reactions, are quite limited [14,15]. Saravanan et al [16] used TPOs as ligands in alcohol oxidations and reported highly selective catalytic oxidation of primary and secondary alcohols to the corresponding carbonyl compounds by utilizing molecular oxygen under mild conditions. The palladium-catalyzed oxidation of alcohols to aldehydes and ketones is indicated in Reaction 1.…”
Section: Organometallic Catalystsmentioning
confidence: 99%
“…A large number of catalyst systems have been developed for the aerobic selective oxidation of alcohol. Among them, supported noble metals including Au,, Pd, Pt,, and their alloys,, have been generally recognized as the most efficient catalysts. Moreover, as heterogeneous catalysts, such supported composites are convenient in catalyst−product separation as well as catalyst recycling.…”
Section: Introductionmentioning
confidence: 99%
“…Different complexes and salts of transition metals, such as Fe [29], Ru [30], Co [31], Cu [32], and Au [33] have been employed for this useful reaction. However, in comparison with the other transition metals, palladium [34][35][36][37][38][39][40] is one of the best efficient catalyst for the aerobic oxidation of alcohols under homogeneous or heterogeneous reaction conditions . Due to contaminants of toxic palladium with products and also high price of palladium catalysts, recently many heterogeneous palladium catalysts have been developed for oxidation reaction of alcohols [62][63][64][65][66][67][68][69][70][71][72].…”
Section: -Introductionmentioning
confidence: 99%